IMPLEMENTASI SWOT ANALISIS TERHADAP STRATEGI PEMASARAN DIMASA PANDEMI COVID-19 PADA UMKM KHAS DESA SUSUKAN TIRTAYASA KABUPATEN SERANG BANTEN - Suwiro Heriyanto; Uli Wildan Nuryanto; Ika Pratiwi; Joni Prihatin (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
Kropcok is a typical snack of seran district which is a source of income for many entrepreneurs, but during the Covid19 pandemic there are challenges in terms of marketing and other internal and external challenges. This research uses a qualitative description method with  the aim of analyzing data descriptively to elaborate other external and internal impacts and determine marketing strategies that can be applied. The sample of this survey is  the  well-known Mafada Kropcok company in Susukan Village, Tirtayasa District.  The data collection method used is a structured  interview and analysis using the TOWS matrix with four alternative strategies. This allows businesses to get solutions such as social media advertising with engaging content and find detailed solutions to expand the delivery network, maintaining good relationships with raw material suppliers.  Based on the results of the analysis of the internal environment with  the IFAS Matrix,it is found that the most influential strength is the quality of the product free of preservatives, and the most influential drawback is the unattractive packaging design. The results of the analysis of the external environment are established using the EFAS matrix, but the most influential opportunity factor is the development of technological progress, and the threat factor is the emergence of new competitors. The results of  the analysis using SWOT show that Mafida Kropcok's position is in the first quadrant, namely through the application of an aggressive growth strategy or growth oriented strength